Housing and feeding management practices and research on artificial kid rearing – A review: Part 1. Artificial feeding of goat kids - Kovács, Levente; Pajor, Ferenc; Tőzsér, János; Póti, Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
In Hungary, the major income of goat keepers comes from milk yield. However, housing kids together with their dams during the suckling period decreases the income from milk sales not only because the suckled milk but also the residual milk amount as well as udder health problems. Nowadays, in the USA, in Australia, in New-Zeeland and in most of the West European dairy goat farms, alternative rearing systems can be applied in order to provide the maximum marketable milk yield during the suckling period and thus to increase farm profitability. The advantages include reduced costs, increased milk production, and breaking disease cycles. Recent studies on milk feeding and weaning methods for goat kids suggest that kids can be reared economically using milk replacers and weaned earlier than the traditional weaning age of 3 months. Kids can be successfully weaned at 9 kg of body weight, 6-8 weeks of age. Although the utilisation of milk replacers for lambs and calves became widespread till this time, there is limited information on young goats. Thus, the purposes of the present review were collect and evaluate such advisements of feeding technologies and recent international research data which may be adaptable for the Hungarian goat keepers applying the artificial methods of rearing goat kids.
Keywords: artificial kid rearing; milk replacer; feeding; housing technology